Exploring C++ The Programmer's Introduction to C++ - Lischner, Ray (Apress : Imprint: Apress, 2009)
Exploring C++ uses a series of self-directed lessons to divide C++ into bite-sized chunks that you can digest as rapidly as you can swallow them. The book assumes only a basic understanding of fundamental programming concepts (variables, functions, expressions, statements) and requires no prior knowledge of C or any other particular language. It reduces the usually considerable complexity of C++. The included lessons allow you to learn by doing, as a participant of an interactive education session. You'll master each step in one sitting before you proceed to the next. Author Ray Lischner has designed questions to promote learning new material. And by responding to questions throughout the text, you'll be engaged every step of the way.